2006
DOI: 10.1111/j.1365-2230.2006.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of basal cell carcinoma by surveyed dermatologists in Scotland

Abstract: In general, BCCs are managed according to BAD guidelines in Scotland, but waiting times vary considerably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Surgery is still considered the first‐line treatment and is by far the most frequent treatment option in various European countries . Standard excision is an effective treatment for all primary BCCs, with a 5‐year recurrence rate of 2–10% .…”
Section: Resultsmentioning
confidence: 99%
“…Surgery is still considered the first‐line treatment and is by far the most frequent treatment option in various European countries . Standard excision is an effective treatment for all primary BCCs, with a 5‐year recurrence rate of 2–10% .…”
Section: Resultsmentioning
confidence: 99%
“…4 Surgery is still considered the first-line treatment in different European countries, and 57-87% of all BCCs are still treated by standard excision (SE). [5][6][7][8] In the current observational literature, 5-year recurrence rates for Mohs micrographic surgery (MMS) are reported to be 1Á0-6Á5% for primary BCC and 4Á0-10Á0% for recurrent tumours. 9-15 A large, 10-year followup randomized controlled trial of high-risk facial BCCs showed a difference of 7Á8% for primary and 9Á6% for recurrent BCCs in favour of MMS over SE, although only the latter reached statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…Reported rates of incomplete excision after routine excision ranges from 1.9% to 16% (Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In a recent study by Leibovitch and colleagues of Mohs micrographic surgery (MMS) in Australia, 11,127 BCC cases were referred for MMS; the reason for referral in 33.1% cases was tumor recurrence. 17 Factors contributing to incomplete excision include difficulty in establishing clinical margins, especially when prior cryotherapy has destroyed tissue architecture, and in certain histologic subtypes with poorly defined macroscopic borders.…”
Section: Ncomplete Excision Of Basal Cell Carcinoma (Bcc)mentioning
confidence: 99%